2014
DOI: 10.1371/journal.pone.0107117
|View full text |Cite
|
Sign up to set email alerts
|

Tomato ABSCISIC ACID STRESS RIPENING (ASR) Gene Family Revisited

Abstract: Tomato ABSCISIC ACID RIPENING 1 (ASR1) was the first cloned plant ASR gene. ASR orthologs were then cloned from a large number of monocot, dicot and gymnosperm plants, where they are mostly involved in response to abiotic (drought and salinity) stress and fruit ripening. The tomato genome encodes five ASR genes: ASR1, 2, 3 and 5 encode low-molecular-weight proteins (ca. 110 amino acid residues each), whereas ASR4 encodes a 297-residue polypeptide. Information on the expression of the tomato ASR gene family is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 75 publications
2
42
1
Order By: Relevance
“…Similar to that in the grape, the ASR in tomato and strawberry also have the His region at its 5 0 terminus, ABA/WDS signatures, and one putative signal for nuclear targeting at its 3 0 terminus ( Figure S6). There are numerous reports on the biochemical and physiological changes of ASR (Dai et al, 2011;Golan et al, 2014;Henry et al, 2011); however, specific findings on the mechanism of the ASR gene involved in the fruit ripening are limited. In 2008, Shkolnik and Bar-Zvi have shown that tomato SlASR1 could abrogate the response to ABA and glucose in Arabidopsis by competing with ABI4 for DNA binding; based on the report, we selected FaASR and SlASR1 to research.…”
Section: Cloning and Gene Expression Patterns Of Asrmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to that in the grape, the ASR in tomato and strawberry also have the His region at its 5 0 terminus, ABA/WDS signatures, and one putative signal for nuclear targeting at its 3 0 terminus ( Figure S6). There are numerous reports on the biochemical and physiological changes of ASR (Dai et al, 2011;Golan et al, 2014;Henry et al, 2011); however, specific findings on the mechanism of the ASR gene involved in the fruit ripening are limited. In 2008, Shkolnik and Bar-Zvi have shown that tomato SlASR1 could abrogate the response to ABA and glucose in Arabidopsis by competing with ABI4 for DNA binding; based on the report, we selected FaASR and SlASR1 to research.…”
Section: Cloning and Gene Expression Patterns Of Asrmentioning
confidence: 99%
“…Analysis of ASR proteins in Loblolly pine and melon has shown that a putative nuclear targeting signal is present at the C-terminus of ASR protein (Canel et al, 1995;Carrari et al, 2004;Chang et al, 1996). The expression of the ASR gene varies among different species, organs and conditions (Golan et al, 2014). Although the ASR gene has been well characterized, the mechanism of ASR in response to fruit ripening at the molecular level is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, this increase occurs in tobacco and tomato by osmotic and drought stress; 4,16,[20][21][22] in rice by drought, saline and osmotic stress; 10,23,24,25 and in plantain and banana by osmotic and biotic stress. 11,26,27 Only a few physiological studies with transgenic tomato, 28 tobacco, 22 maize, 29 and rice 18 plants have proved the involvement of ASR1 in stress tolerance.…”
Section: Functional Roles Of Asr1mentioning
confidence: 99%
“…Beyond this point, the seed maturation stage starts with the characteristic dehydration process. In the turning stage tomatoes, Al treatment induced a higher abundance level of ABSCISIC ACID STRESS RIPENING1 protein 1 (ASR1), which is a low molecular weight plant-specific protein encoded by a salt-, drought- and ABA-regulated gene [48,49,50]. Additionally, the Al-treated red tomatoes were also more enriched with hydrophilic proteins, as well as stress proteins.…”
Section: Discussionmentioning
confidence: 99%